Perturbation-Based Nulling Control Beamforming With Measured Element Radiation Patterns for MU-mMIMO - Yuanzhe Gong; Arish Yaseen; Tingrui Zhang; Robert Morawski; Tho Le-Ngoc (IEEE Open Journal of Vehicular Technology)
A perturbation-based nulling control beamforming (PNCB) scheme is proposed to effectively mitigate multi-user interference (MUI) in multi-user massive multiple-input multiple-output (MU-mMIMO) systems. This is achieved through the precise alignment of deep and wide radiation nulls in the potential interference directions, considering the realistic heterogeneous element radiation patterns (ERPs). Utilizing measured ERPs from an 8 × 8 antenna array prototype, this study conducts a thorough analysis of ERP variations across different positions in the array. The ERP symmetry knowledge is leveraged to enhance the optimization efficiency by reapplying optimized beamforming vectors to symmetric sub-arrays. The proposed PNCB scheme initiates optimization with weights derived from the linearly constrained minimum variance approach, followed by strategic weight perturbations implemented with particle swarm optimization. This process fine-tunes the sub-optimal beamforming vectors to address discrepancies caused by non-uniform ERPs. Illustrative results demonstrate interference suppression levels exceeding 52.4 dB in multi-user scenarios, without significantly affecting the main-lobe radiation patterns. The nulling width control algorithm achieves an average nulling level ranging from −45.3 dB to −57.7 dB across a 6-degree angle span. Further studies delve into the impact of attenuator and phase-shifter quantization on the nulling level, offering insights into performance variations with different hardware configurations. Experimental validation in an anechoic chamber, involving two users with distinct 20 MHz modulation signals, confirms the effectiveness of the proposed PNCB approach, ensuring reliable and efficient communication in MU-mMIMO systems. The results demonstrate an average enhancement of 22.0 dB in the signal-to-interference ratio, effectively reducing the MUI to near the noise floor. The efficacy of the proposed PNCB scheme is further evidenced by the high-quality received constellation diagrams, with enhanced error vector magnitude performance.